2017
DOI: 10.1021/acs.jpcc.7b02345
|View full text |Cite
|
Sign up to set email alerts
|

Blocking Hot Electron Emission by SiO2 Coating Plasmonic Nanostructures

Abstract: Noble metallic nanostructures provide a platform for high-sensitivity spectroscopic sensing with significantly enhanced electromagnetic fields due to surface plasmon polaritons. However, target molecules can be transformed into other molecules under irradiation with an excitation laser during the surface-enhanced measurement, which thus disturbs detection of unknown samples. In this paper, we perform Raman measurements of p-aminothiophenol on gold nanosurfaces with and without deposition of SiO 2 thin films at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 41 publications
(47 reference statements)
1
17
0
Order By: Relevance
“…The increased photostability of the Ag SHINs (compared to bare Ag NPs) is advantageous in the context of plasmon-assisted catalysis. Yet, it is ambiguous whether the nonporous SiO 2 coating allows plasmon-driven chemistry at all or if it blocks the hot electrons that are required to trigger such reactions. In other words, it is not clear if nanostructures protected with a silica shell are useful at all for plasmon-assisted photocatalysis. Figure shows that plasmon-induced reactions can indeed be driven at the Ag/SiO 2 /Au interface, as exemplified for SAMs of two thiols: PNTP (a standard model reactant in plasmon-driven catalysis) and 4-PBTthe Raman probe used throughout this study.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The increased photostability of the Ag SHINs (compared to bare Ag NPs) is advantageous in the context of plasmon-assisted catalysis. Yet, it is ambiguous whether the nonporous SiO 2 coating allows plasmon-driven chemistry at all or if it blocks the hot electrons that are required to trigger such reactions. In other words, it is not clear if nanostructures protected with a silica shell are useful at all for plasmon-assisted photocatalysis. Figure shows that plasmon-induced reactions can indeed be driven at the Ag/SiO 2 /Au interface, as exemplified for SAMs of two thiols: PNTP (a standard model reactant in plasmon-driven catalysis) and 4-PBTthe Raman probe used throughout this study.…”
Section: Resultsmentioning
confidence: 99%
“…The increased photostability of the Ag SHINs (compared to bare Ag NPs) is advantageous in the context of plasmon-assisted catalysis. Yet, it is ambiguous whether the nonporous SiO2 coating allows plasmon-driven chemistry at all, or if it blocks the hot electrons that are required to trigger such reactions[47][48][49][50] . In other words, it is not clear if nanostructures protected with a silica shell are useful at all for plasmon-assisted photocatalysis.Fig.…”
mentioning
confidence: 99%
“…5961 It is known that coating a surface with a thin layer of SiO 2 can prevent hot electrons from reaching or escaping the surface. 62 However, in the case of coating the metal tip with such a layer, we have previously shown that this diminishes the EM enhancement and resulting TERS compatibility of the tip. 23 As the use of silver nanoplates with gap-mode TERS is limited, 15,16 it is difficult to ascertain if this effect occurs exclusively with silver nanoplates.…”
Section: Resultsmentioning
confidence: 99%
“…Many attempts have been made to understand the plasmon-mediated chemical reaction with SERS enabling the monitoring of the chemical transformation of a molecular structure when the molecules are bound to the surface. para -Aminothiophenol ( p -ATP) has been especially studied, which is chemically transformed into 4,4′-dimercaptoazobenzene (DMAB) during SERS measurement. The reaction may depend on the resonant condition. For example, Wang et al have investigated the plasmon-driven surface catalysis reaction of p -ATP to DMAB in Au/Ag NP-film gaps .…”
Section: Introductionmentioning
confidence: 99%